Active‐distributed temperature sensing to continuously quantify vertical flow in boreholes. Issue 5 (6th May 2014) - Read, T.; Bour, O.; Selker, J. S.; Bense, V. F.; Borgne, T. Le; Hochreutener, R.; Lavenant, N.
Abstract We show how a distributed borehole flowmeter can be created from armored Fiber Optic cables with the Active‐Distributed Temperature Sensing (A‐DTS) method. The principle is that in a flowing fluid, the difference in temperature between a heated and unheated cable is a function of the fluid velocity. We outline the physical basis of the methodology and report on the deployment of a prototype A‐DTS flowmeter in a fractured rock aquifer. With this design, an increase in flow velocity from 0.01 to 0.3 m s−1 elicited a 2.5°C cooling effect. It is envisaged that with further development this method will have applications where point measurements of borehole vertical flow do not fully capture combined spatiotemporal dynamics.